WATER IN THE LOWER CRUSTAL GRANULITE XENOLITHS FROM NUSHAN, EASTERN CHINA - Xia Q.K.; Yang X.Z.; Sheng Y.M.; Hao Y.T.; Deloule E. (My University, 2006)
Nominally anhydrous clinopyroxene (cpx), orthopyroxene (opx), and plagioclase (pl) from 10 lower crustal granulite (two-pyroxene granulite and hypersthene granulite) xenoliths in Cenozoic basalts from the Nushan volcano, eastern China, have been analyzed for their hydrogen content by microscopic Fourier transform infrared spectroscopy (Micro-FTIR). The results demonstrate that hydrogen was incorporated in all these minerals in the manner of OH and that the content (H2O weight) is up to 2360 ppm for cpx, 1170 ppm for opx, and 880 ppm for pl. On the basis of the water content of constitutive minerals and their proportions, whole rock water contents of the Nushan granulites were estimated to be 150-950 ppm. Estimated equilibrium temperatures of the Nushan granulites are in the range of 810-892°C, corresponding to the lowermost crust at Nushan (about 25-30 km). Therefore this study provides direct evidence that the lower continental crust, even the lowermost part devoid of hydrous minerals, can contain a certain amount of water in nominally anhydrous minerals. Copyright 2006 by the American Geophysical Union.